The Relationship Between Medication Adherence Based on the Morisky Medication Adherence Scale 8 (MMAS-8) and the Degree of Disease Activity Based on the Disease Activity Score-28 (DAS28) in Rheumatoid Arthritis Patients at Royal Prima Hospital - Putri Amanda Anggraini Harahap; Herlina Yani; Andre Budi (International Journal of Health and Pharmaceutical (IJHP), 2025)
Rheumatoid arthritis (RA) poses a major health challenge due to poor medication adherence impacting disease control. This study aimed to analyze the relationship between medication adherence (MMAS-8) and disease activity (DAS28) in RA patients. A quantitative cross-sectional design was employed at RS Royal Prima Medan (May-July 2025), targeting outpatient RA patients with consecutive sampling (n=69). Data were collected using validated MMAS-8 and DAS28-CRP instruments, analyzed via Kolmogorov-Smirnov normality tests and Spearman's correlation. Results showed moderate adherence (47.8%), low disease activity predominant (31.9%), and significant moderate positive correlation (r=0.400, p<0.001). Higher adherence is linked to better disease control. Conclusion: Medication adherence moderately influences RA disease activity; multifaceted interventions are recommended.